Diet of Arctic char and brown trout in Northern Sweden : potential effects of burbot and lake area - Dagman, Sebastian (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2023)
To manage and conserve different fish species, it is important to know what factors affect the presence and performance of the species. Relatively few studies have focused on burbot and how they interact with other species. In this study I investigate how burbot may be affecting two common salmonids in the arctic and subarctic regions, Arctic char and brown trout. I do this by looking at how the salmonids diets change with- and without burbot presence, and if burbot seem to predate on small salmonids. Additionally, I will also investigate the impact of lake area, since it is an additional factor that can affect fish diets. Eight lakes located in the subarctic region containing Arctic char and brown trout were sampled. Previous studies have found that Arctic char is sensitive to brown trout and burbot competition. The result in this study aligns with that since the Arctic char diet seemed to change more than the brown trout diet when interacting with burbot. Arctic char fed more in the littoral zone when burbot were present, as their diet consisted to a higher extent of large bottom-living invertebrates. But they also fed more on terrestrial insects, which can be found on the lake's surface. This could indicate that Arctic char get more opportunistic in their search for food. Arctic char unexpectedly seems to eat less pelagic zooplankton when burbot is present, but this could be due to them being more opportunistic. Brown trout diet did not seem to be affected by the presence of burbot. Lake area was important for both Arctic char and brown trout diets. Arctic char seemed to eat more Mysis in bigger lakes, but Mysis was not found in all lakes which could be causing this difference. Brown trout seemed to eat more terrestrial insects in bigger lakes and more molluscs in smaller lakes. Burbot predation effects on salmonids seemed to be minor since no fish were found in the stomach content of the burbot in this study. However, only 9 larger individuals (>25cm) were examined, so no strong conclusions can be ...